A Rare T2-T3 Synovial Facet Cyst Causing Progressive Myelopathy - Mohamed F. Albana; Sean Z. Griffiths; Kris E. Radcliff (Case Reports in Orthopedics)
Intraspinal extradural synovial cysts are a rare occurrence at the spinal cord level and thus a rare cause of myelopathy. Synovial cysts usually present in the more mobile lumbar and cervical parts of the spine; however, they may also arise in the thoracic spine. We present a case of a 59-year-old male with a left upper thoracic synovial cyst at T2-3 causing disabling, progressive myelopathy, and an incomplete spinal cord injury syndrome with inability to ambulate. An urgent decompressive laminectomy with bilateral facetectomies, cyst excision, and posterior fusion was performed. Subsequently, the patient recovered full function. Synovial cysts should be considered in the differential diagnosis of progressive thoracic myelopathy. This is only the sixth reported case of a synovial cyst of this kind occurring between the levels of T1 and T7. Urgent surgical decompression is the recommended treatment.